ChemInform Abstract: Porous Polymer Catalysts with Hierarchical Structures. Issue 42 (October 2015) - Sun, Qi; Dai, Zhifeng; Meng, Xiangju; Xiao, Feng‐Shou
Abstract Review: design, syntheses, and catalytic properties; 50 refs.